2010
DOI: 10.1002/cncr.25485
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CD151 as an adverse marker for intrahepatic cholangiocarcinoma patients

Abstract: BACKGROUND:Previous studies have indicated that CD151, a hydrophobic protein, forms a functional complex with the proto‐oncogene that encodes an N‐methyl‐N′‐nitro‐N‐nitroso‐guanidine (MET) protein (c‐Met), and CD151 overexpression reportedly is involved in metastasis/invasion of several tumors. The objective of the current study was to investigate the expression and role of CD151 and/or c‐Met in intrahepatic cholangiocarcinoma (ICC).METHODS:Sixty ICC tissues with matched nontumorous tissues and 20 normal liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 22 publications
1
39
1
Order By: Relevance
“…Previous studies of c-Met expression in bile duct cancer reported broad range of positivity; 12-58 % in IHBD cancer, and 0-68 % in EHBD cancer [4,[13][14][15][16][17]23]. As Miyamoto et al [17] interpreted, this was probably attributed to the small numbers of cases studied, or to differences in the definition of positivity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies of c-Met expression in bile duct cancer reported broad range of positivity; 12-58 % in IHBD cancer, and 0-68 % in EHBD cancer [4,[13][14][15][16][17]23]. As Miyamoto et al [17] interpreted, this was probably attributed to the small numbers of cases studied, or to differences in the definition of positivity.…”
Section: Discussionmentioning
confidence: 97%
“…As the molecular mechanism of carcinogenesis has been better understood recently, receptor tyrosine kinases, such as mesenchymal-epithelial transition factor (c-Met), epidermal growth factor receptor (EGFR), and vascular endothelial growth factor (VEGF), have emerged as prognostic factors or promising targets for treatment in bile duct cancer [2][3][4]. c-Met is a transmembrane receptor tyrosine kinase, and binds with high affinity to its only known ligand, the hepatocyte growth factor (HGF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, high levels of CD151 are correlated with poor prognosis in a variety of tumours including epithelial malignancies such as carcinomas of the lung, 68 breast (invasive ductal carcinoma), 34,53,69 colon, 70 pancreas, 71 kidney, 10 prostate (PCa), 72 liver 73,74 and oesophagus (SCC), 75 as well as glioblastoma. 76 As in most cancers an elevated level of CD151 expression is associated positively with a high tumour grade (Table 1), the assumption that CD151 is involved in cancer progression is well grounded.…”
Section: Clinical Aspects Of Cd151 Expressionmentioning
confidence: 99%
“…Indeed, overexpression of CD151 at the primary site was found to correspond with the development of metastases, mostly in lymph nodes. 53,71,[73][74][75] Formation of secondary tumours in distant organs such as lungs and bone was also noted in clear cell renal carcinoma (RCC). 10 CD151 is implicated as a potential diagnostic marker in osteosarcoma and prostate cancer.…”
Section: Clinical Aspects Of Cd151 Expressionmentioning
confidence: 99%